2018
DOI: 10.1111/apa.14540
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a labour companionship model in three public hospitals in Arab middle‐income countries

Abstract: Aim: To assess the feasibility, acceptability, effectiveness and cost of the integration of a tailored labour companionship model in three public hospitals in Egypt, Lebanon and Syria.Methods: Phased implementation research using mixed methods. Implementation strategies consisted of steering committees in hospitals, seminars for healthcare providers, information, education and communication materials, and adjustments in labour rooms. The labour companionship model consisted of (i) identification of a female re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
(33 reference statements)
4
25
3
Order By: Relevance
“…A study in three Arab countries found that women who had better preparedness for birth had a higher likelihood of companionship during labor. 26 Consistent with other studies on the effect of companionship during labor on intrapartum care, companionship during labor facilitates spontaneous vaginal delivery and reduces the intensity of pain 27 and maternal satisfaction. 28 Given the global epidemic of unnecessary cesarean birth, increasing coverage of nonclinical interventions such as companionship during labor can reduce the risk of unnecessary cesarean births.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study in three Arab countries found that women who had better preparedness for birth had a higher likelihood of companionship during labor. 26 Consistent with other studies on the effect of companionship during labor on intrapartum care, companionship during labor facilitates spontaneous vaginal delivery and reduces the intensity of pain 27 and maternal satisfaction. 28 Given the global epidemic of unnecessary cesarean birth, increasing coverage of nonclinical interventions such as companionship during labor can reduce the risk of unnecessary cesarean births.…”
Section: Discussionsupporting
confidence: 85%
“…Our study showed that women who had prepared for delivery at a health institution had a higher likelihood of companionship during labor. A study in three Arab countries found that women who had better preparedness for birth had a higher likelihood of companionship during labor …”
Section: Discussionmentioning
confidence: 99%
“…This often involved identifying factors that might help or hinder implementation via stakeholder interviews or focus groups [126,127,171,178,182]. Many of these efforts informed policies, guidelines and/or implementation plans [116,124,125,172,182].…”
Section: Theories Models and Framework: Absentmentioning
confidence: 99%
“…For example, an implementation research study conducted in Syria, Egypt and Lebanon used participatory approaches to develop and implement a tailored labour companionship model and reported improvements in acceptability of labour companions among health workers and women's satisfaction with care during childbirth. 9 There are important components of labour companionship implementation that need to be taken into consideration. Creating physical spaces in health facilities or structuring labour wards that support companionship may also be important, such as ensuring the availability and use of privacy measures (curtains/dividers) and a chair for the companion.…”
mentioning
confidence: 99%